DNA methylation profiling in MEN1-related pancreatic neuroendocrine tumors reveals a potential epigenetic target for treatment. Issue 3 (September 2018) - Conemans, E B; Lodewijk, L; Moelans, C B; Offerhaus, G J A; Pieterman, C R C; Morsink, F H; Dekkers, O M; de Herder, W W; Hermus, A R; van der Horst-Schrivers, A N; Drent, M L; Bisschop, P H; et al.
Abstract : Objective: Epigenetic changes contribute to pancreatic neuroendocrine tumor (PanNET) development. Hypermethylation of promoter DNA as a cause of tumor suppressor gene silencing is a well-established oncogenic mechanism that is potentially reversible and therefore an interesting therapeutic target. Multiple endocrine neoplasia type 1 (MEN1) is the most frequent cause of inherited PanNETs. The aim of this study was to determine promoter methylation profiles in MEN1-related PanNETs. Design and methods: Methylation-specific multiplex ligation-dependent probe amplification was used to assess promoter methylation of 56 tumor suppressor genes in MEN1-related ( n  = 61) and sporadic ( n  = 34) PanNETs. Differences in cumulative methylation index (CMI), individual methylation percentages and frequency of promoter hypermethylation between subgroups were analyzed. Results: We found promoter methylation of a large number of potential tumor suppressor genes. CMI (median CMI: 912 vs 876, P  = 0.207) was the same in MEN1-related and sporadic PanNETs. We found higher methylation percentages of CASP8 in MEN1-related PanNETs (median: 59% vs 16.5%, P  = 0.002). In MEN1-related non-functioning PanNETs, the CMI was higher in larger PanNETs (>2 cm) (median: 969.5 vs 838.5; P  = 0.021) and in PanNETs with liver metastases (median: 1036 vs 869; P  = 0.013). Hypermethylation of MGMT2 was more frequent in non-functioning PanNETs compared to insulinomas (median: 44.7% vs 8.3%; P  = 0.022). Hypermethylation of the Von Hippel–Lindau gene promoter was observed in one MEN1-related PanNET and was associated with loss of protein expression. Conclusion: Promoter hypermethylation is a frequent event in MEN1-related and sporadic PanNETs. Targeting DNA methylation could be of therapeutic value in MEN1 patients with advanced PanNETs.